Stem cell-based approaches to enhance nerve regeneration and improve functional outcomes in vascularized composite allotransplantation. Issue 5 (October 2018) - Tung, Thomas H.; Mackinnon, Susan E.
Abstract : Purpose of review: The current review will discuss the current understanding of nerve regeneration in vascularized composite allotransplantation (VCA). The success of proximal arm and leg transplants has been hampered by the limitations of nerve regrowth across long distances resulting in poor regeneration and functional recovery. Relevant research in stem-cell therapies to overcome these issues will be reviewed. Recent findings: The effect of rejection on nerve regeneration in the VCA may be unpredictable and may be quite different for the nerve allograft. The issues that limit functional outcome are likely common to both VCA and proximal nerve injuries or replantation. Stem-cell therapies have focused on augmenting Schwann cell function and appear promising. Summary: A better understanding of the effects of transplant rejection on nerve regeneration and function, as well as the factors that affect regeneration over long distances may inform further therapeutic approaches for improvement.